Upper limb tremor variability in elite sport dancers: The influence of competitive simulation - Kulis, S.; Klobuchowski, W.; Skorulski, M.; Pietraszewski, P.; Callegari, B. (Biomedical Human Kinetics, 2025)
Study aim: The aim of the study was to investigate the variability and symmetry of upper limb physiological tremor in elite sport dancers under simulated competitive conditions. Material and methods: Eighteen elite dancers (9 males, 9 females; age:16.1 ± 2.3 years; training experience: 8 ± 2.1 years; body mass: 62.0 ± 10.4 kg; height: 169.8 ± 7.9cm) all members national team and finalists in Polish championship, participated in the study. The experimental protocol involved a two-phase simulated competition, during which participants performed five standard dances in both semifinal and final rounds. Tremor signals were recorded before and after simulation using tri-axial accelerometry in a standardized postural postition. Frequency-domain analysis was conducted to extract tremor amplitude (L) and frequency (F) in two specific bands: 2-5 Hz and 9-14 Hz. Repeated measures ANOVA was used to analyze the effects of condition (pre vs. post), limb side, and gender. Results: Post-simulation tremor amplitude in the 9-14 Hz range increased significantly (p = 0.0003; np2 = 0.60), suggesting the presence of neuromuscular fatigue and possible increased recruitment of fast-twitch muscle fibers. A significant interaction between limb side and gender (p = 0.006; np2= 0.384) revealed asymmetrical tremor only in male participants, with higher post-exercise values in the dominant arm. Conclusions: Physiological tremor may serve as a low-cost, non-invasive biomarker of neuromuscular fatigue and motor asymmetry in competitive dance. Its application could support individualized training monitoring, optimize fatigue management, and injury prevention strategies in sports requiring high motor precision.